Equation of State of Polycrystalline Stishovite Across the Tetragonal‐Orthorhombic Phase Transition. Issue 9 (3rd September 2018) - Buchen, Johannes; Marquardt, Hauke; Schulze, Kirsten; Speziale, Sergio; Boffa Ballaran, Tiziana; Nishiyama, Norimasa; Hanfland, Michael
Abstract: High‐pressure silica polymorphs may contribute to lithologies in Earth's lower mantle. Stishovite, the tetragonal rutile‐type polymorph of SiO2, distorts to an orthorhombic CaCl2 ‐type structure at pressures and temperatures of the lower mantle. We compressed sintered polycrystalline stishovite and determined the unit cell parameters as a function of pressure using synchrotron X‐ray diffraction. The compression behavior of sintered polycrystalline stishovite deviates systematically from previous results on stishovite powder and single crystals. Following an initial stiffening, the bulk modulus of sintered polycrystalline stishovite drops at the ferroelastic phase transition. We analyzed the observed spontaneous strains using Landau theory to predict the complete elastic behavior of sintered polycrystalline silica across the phase transition. The reduction in bulk modulus at the phase transition as derived here from the compression curve of sintered polycrystalline silica may have implications for the seismic detection of silica‐rich materials in Earth's lower mantle. Plain Language Summary: When rocks from Earth's surface sink into Earth's deep interior, the component minerals change in response to the high pressures and high temperatures. Among others, a mineral called stishovite forms. Stishovite has the same chemical formula as quartz but a higher density. At depths beneath 1, 500 km, the stishovite crystals distort spontaneously to adapt to higher pressures. Because of this inherent tendency of the crystals to distort, they become elastically softer close to the pressure at which they distort spontaneously. We measured the compressibility of stishovite at high pressures and found that stishovite is less compressible when many stishovite crystals are firmly connected to each other. When the crystals distort, however, the polycrystalline material suddenly becomes more compressible again. Because seismic waves travel slower in elastically soft and compressible materials, we conclude that seismic waves might be slowed down by stishovite close to those pressures or depths where the stishovite crystals distort. The change of the elastic properties of stishovite might even result in seismic waves bouncing off rocks that contain stishovite. Such seismic waves can be detected on Earth's surface and may be used to infer the presence of stishovite in Earth's lower mantle. Key Points: We compressed sintered polycrystalline stishovite across the ferroelastic tetragonal‐orthorhombic phase transition The compression behavior of sintered polycrystalline stishovite deviates systematically from powder The bulk modulus of sintered polycrystalline stishovite drops at the ferroelastic phase transition